DISKURSUS PERKAWINAN BEDA AGAMA DI INDONESIA DALAM TINJAUAN UNIVERSALISME HAM DAN RELATIVISME BUDAYA - Fitrawati Fitrawati (JURIS (Jurnal Ilmiah Syariah), 2021)
This paper tries to examine the right to freedom of interfaith marriage in Indonesia from the perspective of Human Rights Universalism and Cultural Relativism. The purpose of this paper is to explain how universalism and cultural relativity view interfaith marriage in Indonesia. This research is a normative legal research. This study uses a literature approach. The findings of this study indicate that interfaith marriage in Indonesia is still not well accepted and has always been controversial news in the community, even considered to have exceeded or violated the provisions of marriage, but there are still followers of different religions who decide to marry. In fact, many of them are smuggling laws so that their marriages are recognized by the state, namely by registering marriages abroad and then continuing the registration in Indonesia. Meanwhile, on the other hand, Indonesia already has a law on Marriage, namely, Article 2 paragraph 1. It is also contained in the article of the Universal Declaration of Human Rights, namely the right to freedom of marriage (article 16 UDHR) which includes the right to marry between religions (different religions), and the right to freedom of religion (article 18 UDHR) which includes the right to change religions. Meanwhile, in cultural realivism, it rejects everything that is universal.